2022
DOI: 10.32604/or.2022.027277
|View full text |Cite
|
Sign up to set email alerts
|

The Implication of microRNAs as non-invasive biomarkers in 179 Egyptian breast cancer female patients

Abstract: Background: MicroRNAs (miRs) are small (19-25 nucleotides), non-protein coding RNAs that regulate gene expression, and thus play essential roles in cell cycle progression. The evidence has demonstrated that the expression of several miRs is dysregulated in human cancer. Methods: The study includes 179 female patients and 58 healthy women Patients were identified as luminal A, B, Her-2/neu, and basal-like, as well as classified into I, II, and III stages. Analysis of the expression fold change of miR-21 and miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The LPS-BJ-1 ΔΔCt was calculated by subtracting the ΔCt of the interested gene (BJ-1 cells before LPS treated) from the ΔCt of each interested gene (BJ-1 cells post LPS treated). The PVA/AH LPS-BJ-1 ΔΔCt was calculated by subtracting the ΔCt of the interested gene (LPS-BJ-1 cells before PVA/AH treated) from the ΔCt of each interested gene (LPS-BJ-1 cells post PVA/AH treated).The formula 2 −ΔΔCt was used to get the fold change ( 39 42 ).…”
Section: Methodsmentioning
confidence: 99%
“…The LPS-BJ-1 ΔΔCt was calculated by subtracting the ΔCt of the interested gene (BJ-1 cells before LPS treated) from the ΔCt of each interested gene (BJ-1 cells post LPS treated). The PVA/AH LPS-BJ-1 ΔΔCt was calculated by subtracting the ΔCt of the interested gene (LPS-BJ-1 cells before PVA/AH treated) from the ΔCt of each interested gene (LPS-BJ-1 cells post PVA/AH treated).The formula 2 −ΔΔCt was used to get the fold change ( 39 42 ).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis included examining the variations in mRNA target content concerning the glyceraldehyde-3-phosphate dehydrogenase gene, which was normalized. This analysis was conducted using the comparative cycle threshold approach designated by Livak and Schmittgen [38][39][40][41] .…”
Section: Real-time Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…The results of the statistical analysis showed in figure (1) that there are significant differences in the toxicity of the plant extracts according the type of plant extract used. It was observed that the mortality percentage increase with increasing concentration and that there is a difference between the plants in the occurrence of the deadly effect so that the plant extract exceed to another , In the quality and quantity of the active compounds that are contained in different plants which affect in the nervous system of the insect, which paralyzes the movement leading to shock and death, as well as the impact on the work of enzymes necessary for the vital processes, which lead to the cessation of metabolism and thus Death [10]. The results of the table (1) showed that the extract of the seeds of the Helianthus annuus L. gave the highest effect in mortality from the rest of the plant…”
Section: -The Efficacy Of Plant Extracts In Tribolium Castaneum After...mentioning
confidence: 99%